Lichtrouten : Perspektiven in der Stadt des Lichts. - Dakic, Danica; Friebe, Inge; Geldmacher, Klaus; Hergenhahn, Hermelinde; Holmes, Andrew; Hoover, Nan; Hupp, Alexandra; Karbach-Bachmann, Jutta; Lemke, André Philip; Marré, Jörg; Pelz, Bettina; Schmidt, Friedrich Karl; et al. (Lüdenscheid : WKL GmbH Wirtschaftsförderungsgesellschaft, 2002)
Geldmacher, Klaus ; Hartung, Georg ; Hausig, Daniel ; Katase, Kazuo ; Kiessling, Dieter ; Niscino, Tazro ; Dakic, Danica ; Fritsch, Arwed ; Groll, Tom ; Hergenhahn, Hermelinde ; Hofmann, Stefan ; Hoover, Nan ; Hupe, Dirk ; Lemke, André Philip ; Mariotti, Francesco ; Belzner, Uwe ; Holmes, Andrew ; Breil, Christian ; Knappschneider, Uwe ; Pelz, Bettina
biog. p. 84-91, bibliog. p. 92-93
Duits
Lichtrouten, Stadt Lüdenscheid, 20.09. - 06.10.2002
boek